Pengaruh Brand Image dan Kualitas Produk Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Carica Gemilang Di Wonosobo) - Asih Riyanti; Agung Budiatmo (Universitas Diponegoro, 2017)
Brand Image and product quality are some factors can that influence purchasing decisions made by consumers. As a result, the company as much possible should be able to make the brand image and product quality well in the eyes of society this is so that consumer purchasing decisions against a product is high. brand image that strong and product quality reliable will be able to meet the needs and desires of consumers.The type of research is explanatory research where the sample was amounted to 100 people white purposive sampling technique. Data source used is primary data and secondary data, The selected respondents are consumers who did purchasing decision of carica gemilang 2017 year in Wonosobo. The methodology was to analyzing the primary data in this research validity test, reliability test, correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, and Significance test (t and F test) with SPSS 16.0. The result of the research showed that brand image had significant effect on purchasing decision by donating 33,1% and the rest was explained by other factor basides brand image. Product quality had a significant effect to purchasing decision by donating 33,5% and the rest was explained by other factor basides product quality. Meanwhile, simultaneously brand image and product quality had significant effect to purchasing decisionby donating 35,4% and the rest was explained by other factor basides brand image and product quality. This means that the better brand image and product quality, the higher the decision to buy a brilliant carica in Wonosobo. In addition, product quality had the most dominant influence with regression ceofficient value of 0.321. Based on the result of research, researcher suggest UD. Gemilang Kencana re-analyzes the level of consumer loyalty in order to get a better brand image, improve the resulting taste in order to get a better product quality and give a good impression to consumers